Restoring Degraded Landscapes for Sustainable Crop Intensification and Improving the Livelihood Security of the Particularly Vulnerable Tribal Groups in Odisha, India - Anantha K.H.; Garg, K.K.; Venkataradha, A.; Barik, Rashmi Ranjan; Singh, Ramesh; Padhee, K.P.; Nayak, M.; Dhal, N.C.; Arthanari, P.; Jat, Mangi L. (2025)
Land degradation is one of the major challenges that affects about 29% of land area and impacting nearly 3.2 billion people, globally. Land degradation takes many forms and affects soil, forests, biodiversity, water and socio-economic services derived from the ecosystem. Moreover, rapidly changing land use and deforestation in uplands leads to accelerated land degradation and generates large volume of runoff along with high rate of siltation. This runoff loss not only creates water/moisture deficit in uplands but also invades mid- and lowlands of the landscape due to flooding, eutrophication, and heavy siltation in water bodies. These changes have been accompanied by negative externalities such as climate change, loss of biodiversity, poor retention ability of the landscape and heavy land degradation. These alterations have influenced number of planetary boundary conditions which are negatively influencing available natural resources, sustainability, and productivity of the landscape at local, regional, and global scale. These challenges are catastrophic, especially in uplands, those were historically covered with forests however, converted into desolated landscapes over the period. The impact is severe as these landscapes largely belonging to marginal and small landholders which coincide with high poverty and malnutrition. With the absence of resource availability, in habitants residing in these areas are compelled to migrate to urban centres in search of their livelihoods leaving behind their valuables and families. This situation often result in a precarious socio-economic conditions including large scale unemployment and delinquency in the society. However, this also provides an opportunity to harvest surface runoff through sciencebased landscape resource conservation approaches using both engineering and biological measures. This facilitates improving the water retention ability of the landscapes which governs the water availability in surface and groundwater systems that facilitates sustainable intensification and diversification of agri-food system.